2020
DOI: 10.1016/j.psj.2020.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing dietary amino acid density and stocking density on growth performance, carcass characteristics, meat quality, and occurrence of white striping in broiler chickens

Abstract: A 49-day trial was conducted to determine the impact of dietary amino acid ( AA ) density and stocking density ( SD ) on growth performance, carcass traits, meat quality, and white striping ( WS ) occurrence in broiler chickens. Two hundred eighty-eight Ross 308 male broilers consisting of 6 replicate cages with 8 broilers per replicate were used. Treatments were arranged in a 3 × 2 factorial and consisted of 3 AA densities (normal, 10, or 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…High density stocked birds had reduced tibia quality compared to low-density stocked ones (Wang et al, 2020). In addition, Wang et al (2014) observed a reduction in drip loss of broilers breast muscle, triggered by high SD, while Pekel et al (2020) reported that the length of breast filet was significantly increased among stressed broilers. Drip loss can show quality deviations as the volume of drip loss is an indicator of oxidative stress in muscles (Wang et al, 2014).…”
Section: Stocking Density Stress Challengementioning
confidence: 91%
“…High density stocked birds had reduced tibia quality compared to low-density stocked ones (Wang et al, 2020). In addition, Wang et al (2014) observed a reduction in drip loss of broilers breast muscle, triggered by high SD, while Pekel et al (2020) reported that the length of breast filet was significantly increased among stressed broilers. Drip loss can show quality deviations as the volume of drip loss is an indicator of oxidative stress in muscles (Wang et al, 2014).…”
Section: Stocking Density Stress Challengementioning
confidence: 91%
“…Nutrient requirements of Ross 308 broiler chickens recommended by Aviagen (Huntsville, AL, USA, 2019) were used as benchmark. Control group was fed starter (days 0-10), grower (days [11][12][13][14][15][16][17][18][19][20][21][22][23][24], finisher (days [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], and withdrawal (days [40][41][42][43][44][45][46][47][48][49] diets according to the recommendations. Remaining groups received diets as follows:…”
Section: Methodsmentioning
confidence: 99%
“…¶ Each kilogram contained: manganese (as manganese oxide 62%) 150 000 mg; iron (as iron sulfate monohydrate 31%) 120 000 mg; zinc (as zinc oxide 72%) 120 000 mg; copper (as copper sulfate pentahydrate 25%) 12 000 mg; iodine (as calcium iodide 62%) 3000 mg; selenium (4.5%) 225 mg; molybdenum (as sodium molybdate 39%) 750 mg; calcium carbonate 13% (as carrier). starter (days 0-10), grower (days [11][12][13][14][15][16][17][18][19][20][21][22][23][24], finisher (days 25-39), and withdrawal (days [40][41][42][43][44][45][46][47][48][49].…”
Section: Rearing Conditions and Broiler Managementmentioning
confidence: 99%
See 2 more Smart Citations